Analysis of the hard and soft shading impact on photovoltaic module performance using solar module tester - Mustafa Hamid Al-Jumaili; Ahmed Subhi Abdalkafor; Mohammed Qasim Taha (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Solar cells are a major alternate source of sustainable energy in the usual condition of depleting non- renewable energy sources. Nowadays, this source is getting more and more important due to its use in large and small-scale installations. One of the major causes of energy losses in photovoltaic (PV) modules is the shading. It can happen due to clouds passing, near trees, and/or neighboring structures. Generally, there are two types of PV module Shading which are either partial shading or complete shading. Both have a significant impact on the solar module output power. This paper is an attempt of carrying out a study of the electrical characteristics of a solar module with various percentages of simulated shading. The solar module tester (SMT) simulator was used in this study. The study approved the direct correlation between short-circuit current and solar irradiance. The advantage of using SMT is its stable irradiance in comparison to the practical unstable solar irradiance within the same period. The results of both methods of shading simulation show that shading has a significant impact on the performance of solar panel in terms of efficiency, fill factor and output power. For better performance, solar panels should install in shading free places as much as its possible.